Pengaruh Inkuiri Terbimbing Berbantuan Multimedia Interaktif Terhadap Kemampuan Kognitif Siswa Pada Materi Larutan Penyangga dan Sistem Koloid - Aprilia Novira Sodayang; Sonny Lumingkewas (Oxygenius Journal Of Chemistry Education, 2021)
Guided inquiry learning model is a student centered learning model, namely stundents formulate problems, design experiments, collect and analyze data to make their own decision. In the study the guided inquiry learning model combined with iteractive multimedia, interactive multimedia is a fun and learning medium that supports educational development and plays an important role in chemical learnig activities which are still abstract in nature. This study aims to determine how the cognitive abilities of students after learning with guided inquiry assisted by interactive multimedia at SMA Negeri 1 kakas in the 2019/2020 school year. The population in this study was class XI IPA and the sample taken was class XI IPA 1 with a total of 25 students. The research instrument used was a test on students at the end of the lesson. The instrument in this study was a test of students cognitive abilities. Based on data analysis,in the buffer solution material there were 5 out of 25 students who did not reach the KKM standard and on the colloid system material there were 3 out of 25 students who did not reach the KKM standard